Growth Rate and Chlorophyll Content of Liberica Coffee Leaves (Coffea liberica L.) with Addition Rhizosphere Bacterial Microcapsules from Eruption Soil of Mount Sinabung - Warsito, Kabul; Sembiring, Desi Sri Pasca Sari; Irawan, Indra; Kriswanda, Bagus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The chlorophyll content in coffee leaves greatly influences growth productivity and productivity. This study aimed to examine the effect of seed soaking and rhizosphere bacteria microcapsule dosage on the growth rate and chlorophyll content of Liberica coffee leaves planted on peatland. The experiment used a completely randomized design (CRD) with two factors, namely seed soaking time (0, 9, 10, and 11 hours) and rhizosphere bacteria microcapsule dosage (0, 10, 15, and 20 grams), with a total of 16 treatment combinations replicated twice. The parameters measured included leaf area, number of leaves, and chlorophyll content. The results showed that 11-hour seed soaking treatment produced the largest leaf area (40.32 mm), 9–10 hours soaking gave the highest number of leaves (10.34), and 20 grams of microcapsules gave the highest chlorophyll content (79.16 CCI). ANOVA and Duncan's test showed that seed soaking and microcapsules significantly affected the growth and chlorophyll content of leaves. In conclusion, the combination of seed soaking for 9–11 hours and a 20 gram microcapsule dose can improve the growth and quality of Liberica coffee leaves.